Effect of post-harvest forestry residue management practices on the diversity of epigeal coleopterans (2017)
The aim of this work was to study the effect of post-harvest forestry residue management practices on the epigeal coleopterans diversity and abundance in a 1-yr old Pinus radiata plantation. Approximately 25-yr old P. radiata plantation was available, which was harvested by clear-cutting at the beginning of 2010 in Constitución, central Chile. Three post harvest residue management treatments were installed in a fully randomized design in blocks: 1) a control, where residues were intact left; 2) residue removed ( 2.5 cm diameter); and 3) burned. The coleopterans were sampled in spring and summer, using linear transects with pitfall traps. The abundance and richness, and diversity index of coleopterans were determined. A total of 23 species of 13 families were obtained. Both in the springand summer, the treatment with residues left registered significantly greater abundance and species richness. In the residue management, the practices of intact leaving residue should be considered as the least impacting on diversity and abundance of epigeal coleopterans and is recommended for creating refugee areas to promote diversity of beetles in this area of study.